THE INFLUENCE OF CONSUMER PREFERENCES ON PURCHASING DECISIONS OF FROZEN FOOD PRODUCTS âSINDIUNG FOODâ - Maulida, Arifa
Sindiung Food has 3 product variants, namely chicken, duck and quail meat. There are difficulties when determining the stock of goods in one production. This is a changing consumer preference. If it is expected that chicken products are more desirable, Sindiung would produce more chicken than duck and quail meat. However, duck meat sales run out faster than chicken products. Fluctuating sales are the result of mistakes in predicting the market. This research was conducted to find out how the relationship and the influence of consumer preferences on frozen food purchasing decisions from Sindiung Food in Bandung city. This type of research methodology is quantitative with a sample of 145 respondents. The collection of data in this study was done by using a questionnaire given to respondents consisting of dimensions of preference variables namely taste, price, packaging, brand and variable dimensions of Purchasing Decisions, which are Problem Recognition, Information Searching, Alternative Evaluations, Purchase Decisions. Data analysis uses Correlation Analysis and Simple Regression Analysis. From the results of calculations and analysis by the author, it is known that there is a strong relationship between consumer preferences and purchasing decisions seen from the value of R = 0.706 (70.6%). While the influence of consumer preferences on purchasing decisions has an R Square value of 0.498 (49.8%).